(untitled) - Sulgan, Marian; Kubasakova, Iveta (Doprava a spoje, 2010)
This article discusses problems of seeking new opportunities and logistics solution for shipping multimodality, optimize infrastructure capacity, more efficient access to logistics services to small and medium-sized business entities in industry and trade